MELESTARIKAN BUDAYA BANYUMASAN MELALUI DIALEK BAHASA NGAPAK - Isrofiah Laela Khasanah; Heri Kurnia (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2023)
The Banyumas people, who are popularly called wong Banyumasan, are widely known as unique and different figures compared to other Javanese people. The special difference lies in the accent they use, namely the ngapak language. It is called ngapak because the pronunciation of the vowels "a" and "o" and the consonants b, d, k, g, h, y, k, l and w are fixed and not floating or half-assed, as is usually found in standard Javanese. Wong Banyumasan, which consists of Banjarnegara, Purbalingga, Banyumas, Cilacap and Kebumen regencies, makes the ngapak dialect their cultural identity. This research uses a literature study method with a qualitative descriptive research type. The data in this study used secondary data by searching databases from various references, such as research journals, journal reviews, and data related to Banyumasan culture, especially the Ngapak language. Data analysis for this study used descriptive qualitative and analytical descriptive methods. The results of the research show that the Ngapak dialect is the development of thoughts or perceptions in relation to the patterns that exist in the Ngapak dialect itself. The view of the Banyumasan cultural community on the Ngapak dialect is that it is a Banyumasan cultural identity that is unique, cool and rich, and has the potential to be developed. The use of the ngapak dialect in the daily life of the Banyumasan people still shows their consistency not to give up and to preserve their cultural identity. Keywords: Banyumasan culture; Ngapak dialect; cultural identity